Development and deployment of a new robotics toolbox for education. Issue 3 (12th December 2014) - Gil, Arturo; Reinoso, Oscar; Marin, Jose Maria; Paya, Luis; Ruiz, Javier
ABSTRACT This paper presents a new toolbox focussed on the teaching of robotic manipulators. The library works under Matlab and has been designed to strengthen the theoretical concepts explained during the theory lectures. The educational approach is focussed on teaching the main concepts through developing math modeling and simulation. In order to do this, the toolbox aims at the fulfillment of a set of practical sessions that allow the students to test most of the concepts of an introductory course in robotic manipulators. In addition, the library possesses features that typically needed the usage of proprietary software, such as the visualization of a realistic 3D representation of commercial robotic arms and the programming of those arms in an industrial language. The practices include the concepts of direct and inverse kinematics, inverse and direct dynamics, path planning and robot programming. As a transversal practice, during the sessions, the student is asked to choose and integrate a new robotic arm in the library, proposing a particular solution to the direct and inverse kinematic problem, as well as the inclusion of other important parameters. The library has been deployed during the last year in bachelor and master studies and has received a nice acceptance. Finally, the library has been assessed in terms of usefulness, design and usage by means of a student survey. In addition, the surveys were designed to establish a relation between the student perception of the system, the time spent on the tool and their learning achievements. © 2014 Wiley Periodicals, Inc. Comput Appl Eng Educ 23:443–454, 2015; View this article online at wileyonlinelibrary.com/journal/cae; DOI 10.1002/cae.21615